Implication of serum hepcidin level in maintainance haemodialysis patients in association with different iron indices (Bangladesh Medical Journal Khulna, 2022)
Background: Anaemia is a frequent complication in maintenance hemodialysis (MHD) patients and is associated with increased morbidity and mortality. Altered systemic iron metabolism and functional iron deficiency mainly related to subclinical inflammation makes it difficult to maintain proper control of anaemia. The discovery of hepcidin and it's functions has contributed to a better understanding of iron metabolism disorders in CKD anaemia.Objective: To evaluate the association of serum hepcidin with different iron indices (serum iron, serum ferritin, TIBC and TSAT).Materials and Methods: The study was carried out in the Institute of Kidney Diseases and Urology, Dhaka for a period of six months between July to December 2016. Serum hepcidin-25, current iron markers and other laboratory parameters were measured among study subjects. Absolute and functional iron deficiency patients were identified according to serum ferritin and TSAT. Statistical analysis was performed to find out whether serum hepcidin level significantly differ in MHD patients than healthy controls and also to evaluate it's correlation with other iron indices among MHD patients.Results: Total 88 subjects (fifty MHD patients and thirty eight healthy controls) were enrolled into the study. Serum hepcidin level was significantly higher in MHD patients than healthy controls (19.3 (7.0 - 81.8) ng/ml vs 8.0 (2.4 - 33.6) ng/ml, P value